Outcome of a Ceratohyiodectomy in a Criollo Mare with Temporohyoid Osteoarthropathy - Andrade Mousquer, Mariana; Americo Rafael, Leandro; de Oliveira Ferreira, Nathalia; Aires da Silva, Margarida; Scheffer del Pino, Taís; Portela de Assis, Cassiano; da Rosa Curcio, Bruna; Wayne Nogueira, Carlos Eduardo (Acta Scientiae Veterinariae, 2021)
Background: Temporohyoid osteoarthropathy (THO) is a progressive disease that causes acute onset of peripheral vestibular signs with or without facial paralysis. Ankylosis of temporhyoid joint occurs which predispose to fractures of the involved bones and consequently causes the commonly neurological signs observed. Clinical signs vary depending on the stage of the disease and the nerves affected. Surgical treatment is advised to improve survival rates in which the ceratohyoidectomy is currently known as the most advantageous. The aim of the present study is to report a case and outcome of a ceratohyoidectomy procedure in a Criollo mare presenting THO of the right temporohyoid joint. Case: A 17-year-old Criollo mare was referred to the Equine clinical hospital of the Federal University of Pelotas with a 5-day history of facial paralysis on the right side, head tilt and difficulty to chew and swallow. Auricular, palpebral and labial ptosis along with deviation of the lip and nostril to the left were observed. A corneal ulcer was also identified in the right eye. Complementary imaging exams (endoscopy of the guttural pouches and radiography of the head) were performed and showed thickening of the right stylohyoid bone confirming a diagnosis of THO. Anti-inflammatory and antibiotic therapy were administered and the corneal ulcer was treated with topical antibiotics and autologous serum. Due to rapid deterioration of clinical signs, the mare was referred to surgery. A ceratohyoidectomty procedure was performed under general anesthesia. In this procedure, the ceratohyoid bone was disarticulated from the ceratohyoid-basihyoid joint and removed. During the procedure, a branch of the linguofacial vein was accidentally incised causing hemorrhage, the branch was identified and successfully ligated. Recovery was uneventful. Supportive treatment with anti-inflammatory and antibiotics was continued after surgery and two sessions of electro-acupuncture was also performed to improve the nerve paralysis. The electro-acupuncture was discontinued due to mare’s negative behavior on needle insertion in the face. The treatment of the ulcer was changed since no improvement was observed in the first days. Twenty-eight days after hospitalization, the mare was discharged with the ulcer healed and significant improvement of neurological signs. A complete recovery occurred within three months. Discussion: The Criollo mare was referred to the hospital presenting mild neurological signs consistent with vestibular alteration and facial nerve paralysis. The THO diagnosis was confirmed using complementary imaging exams in which the endoscopy of the guttural pouch is considered the most common when computed tomography, a more sensitive one, is not available. Unilateral ceratohyoidectomy was performed as a surgical choice of treatment since it has a higher survival rate and lower recurrence rate in comparison to medical treatment and to stylohyoidectomy. As the main intraoperative complication, a vessel was accidentally incised, however this is described to occur in some cases. Despite that, the procedure was successfully performed and the mare had a complete recovery of the neurological signs and corneal ulcer. In conclusion, this report showed that it is important to have a complete diagnosis of these diseases and a consistent treatment plan to improve patient’s survival and quality of life. Keywords: neurologic disease, peripheral vestibular signs, facial paralysis, ceratohyoid bone, ceratohyoidectomy.